Approximate Analytical Technique to Design Reflectarray Antenna - Yamani, H. M.; Attiya, A. M.; Abdelmageed, A. K. (Advanced Electromagnetics, 2016)
This paper presents an analysis and design for a reflectarray antenna composed of an array of rectangular patches printed on a grounded dielectric slab. A simple analytical technique based on equivalent surface impedance is used to determine the reflection of the elements in reflectarray antenna. This equivalent surface impedance is obtained analytically in a closed form. The effect of the angle of incidence on each element in the reflectarray is included in calculations. To author’s knowledge, this property has not been included in previous analysis techniques of reflectarray antenna.